The IL-25/ILC2 axis promotes lung cancer with a concomitant accumulation of immune-suppressive cells in tumors in humans and mice - Bahhar, Ilham; Eş, Zeynep; Köse, Oğuzhan; Turna, Akif; Günlüoğlu, Mehmet Zeki; Çakır, Aslı; Duralı, Deniz; Magnusson, Fay C. (Frontiers in Immunology, 2023)
Background Group 2 innate lymphoid cells (ILC2) can be activated by interleukin (IL)-33 or IL-25. IL-25-activated ILC2 cells help protect the host against helminth infection while exacerbating allergic-like inflammation and tissue damage in the lung. In the context of cancer, IL-33activated ILC2 cells were found to bear anti-tumoral functions in lung cancer while IL-25activated ILC2 cells promoted tumorigenesis in colorectal cancer. The role of IL-25-activated ILC2 cells in lung cancer remains to be addressed.We examined the overall survival of human non-small cell lung cancer (NSCLC) patients according to IL25 expression as well as the distribution of ILC2 cells and regulatory T cells (Tregs) in various NSCLC patient tissues and peripheral blood (PB) of healthy donors (HDs). We analyzed the effect of adoptive transfer of IL-25-activated ILC2 cells on tumor growth, metastasis and survival in a heterotopic murine model of lung cancer.We report that human NSCLC patients with high IL-25 expression have reduced overall survival. Moreover, NSCLC patients bear increased frequencies of ILC2s compared to HDs.Frequencies of Tregs were also increased in NSCLC patients, concomitantly with ILC2s. In mice bearing heterotopic lung cancer, adoptive transfer of IL-25-activated ILC2s led to increased tumor growth, increased metastasis and reduced survival. The frequencies of monocytic myeloidderived suppressor cells (M-MDSCs) were found to be increased in the tumors of mice that received ILC2s as compared to controls.Conclusions Overall, our results indicate that the IL-25/ILC2 axis promotes lung cancer potentially by recruiting immune-suppressive cells to the tumors both in humans and in mice, and that it may therefore represent a suitable novel target for NSCLC immunotherapeutic development.